Fiber-matrix interface improvement via glycidyl methacrylate compatibilization for rotomolded poly(lactic acid)/agave fiber biocomposites. (January 2021) - Robledo-Ortíz, Jorge Ramón; González-López, Martín Esteban; Martín del Campo, Alan Salvador; Peponi, Laura; González-Nuñez, Rubén; Rodrigue, Denis; Pérez-Fonseca, Aida Alejandra
The growing interest in research and development of eco-friendlier materials makes attractive the use of bio-based and biodegradable polymers such as polylactic acid (PLA). However, the higher cost of PLA compared to conventional polymers limits its applications. Moreover, raw materials for rotational molding must be in a powder form, which further increases their cost. So, the main objective of this study was to use agave fibers to produce lower-cost PLA based rotomolded biocomposites (BC) without compromising its bio-sourced origin and to compare with a standard rotomolding resin: linear medium density polyethylene (LMDPE). To improve the fiber-matrix interface, a chemical surface treatment of the fibers with glycidyl methacrylate grafted polylactic acid (GMA-g-PLA) in solution was evaluated. The results showed that a better biocomposites' morphology was obtained, especially with the fibers treated twice. The surface treatment was also shown to substantially improve the flexural and tensile properties of treated fiber biocomposites at higher fiber content (25% wt.) compared to those with untreated fiber. The surface treatment also led to a substantial reduction of the biocomposites porosity and water absorption. Overall, the samples were shown to have better mechanical properties than neat LMDPE while being eco-friendlier due to their bio-nature.